m5C RNA Methylation Primarily Affects the ErbB and PI3K–Akt Signaling Pathways in Gastrointestinal Cancer - Xiang, Shixin; Ma, Yongshun; Shen, Jing; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Yang, Xiao; Kaboli, Parham Jabbarzadeh; Du, Fukuan; Ji, Huijiao; Zheng, Yuan; Li, Xiang; et al. (Frontiers in Molecular Biosciences, 2020)
5-methylcytosine (m5C) is a kind of methylation modification which occurs in both DNA and RNA and present in the highly abundant tRNA and rRNA. It has important impact on various human diseases including cancer. The function of m5C are modulated by regulatory proteins, including methyltransferases (writers) and special binding proteins (readers). This study aims at comprehensive study the m5c RNA methylation related-genes and figure out the main pathways under m5c RNA methylation in gastrointestinal (GI) cancer. Our research showed that expression of m5C writers and reader were up-regulated in GI cancer. The NSUN2 gene has the highest proportion of mutations found in GI cancer. Importantly, in liver cancer, higher expression of almost all m5C regulators were significantly associated with lower patient survival rate. In addition, the expression level of m5c-related genes are significantly different in the analysis of clinical parameters at the pathological stage. Finally, we have found through bioinformatics analysis that m5C regulatory proteins are closely related to ErbB/PI3K-AKT signaling pathway and have important impact on liver cancer survival and GSK3B may be an important target gene for targeted therapy of GI cancer. Besides, the compound termed Streptozotocin may be a key candidate drug target on GSK3B for molecular targeted therapy in gastrointestinal cancer.